2014
DOI: 10.1088/0953-8984/26/9/095001
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic study of the structural and electronic properties of a-Si:H/c-Si interfaces

Abstract: Abstract. We investigate the structural and electronic properties of the interface between hydrogenated amorphous silicon (a-Si:H) and crystalline silicon (c-Si) by combining tight-binding molecular dynamics and DFT ab inito electrionic stucture calculations. We focus on the c-Si (100) (1×1)/a-Si:H, c-Si(100)(2×1)/a-Si:H and the c-Si(111)/a-Si:H interfaces due to their technological relevance. The analysis of atomic rearrangements induced at the interface by the interaction between H and Si allowed us to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…We also find H atoms in a bridging position (0.2 atoms per simulation cell). Santos et al 25 also investigated this defect but it was not reported by Tosolini et al 6 The number of other defects is less than 0.1 per simulation cell. The differences with Santos et al and Tosolini et al are possibly due to the different method used to prepare the structure: they used tight-binding MD whereas we used DFT MD.…”
Section: Preparation Of the Structurementioning
confidence: 91%
“…We also find H atoms in a bridging position (0.2 atoms per simulation cell). Santos et al 25 also investigated this defect but it was not reported by Tosolini et al 6 The number of other defects is less than 0.1 per simulation cell. The differences with Santos et al and Tosolini et al are possibly due to the different method used to prepare the structure: they used tight-binding MD whereas we used DFT MD.…”
Section: Preparation Of the Structurementioning
confidence: 91%
“…These electrons not only are far away from the nucleus but also sometimes exhibit spin polarization. In the conventional DFT (including LDA and GGA) calculations, the electron-electron repulsion of the Kohn-Sham equations is still based on a singleparticle approximation 57,58 . The electronic exchange function sees spin-pair electrons as single particles, in which case, the number of K-S orbitals is half of the total number.…”
Section: Mott Phase Transitionmentioning
confidence: 99%
“…We also considered structural models for amorphous silicon overlayers, using the same computational setup. In this case, the initial structures were obtained by slicing the atomic positions at a cubic-Si/amorphous-Si interface, as determined by tight-binding molecular dynamics simulations [15], placing it on a 4 × 4 Ag(111) supercell, and performing further geometrical relaxation. This resulted in the structural model shown in Fig.…”
mentioning
confidence: 99%